WORLD EXPERIENCE AND FEATURES ELECTRIFICATION OF RAILWAYS IN UKRAINE - Polishko, T. V. (Science and Transport Progress, 2009)
The history of development of electrification of railways in the world, Russia and Ukraine is considered. The specific amount of transportations on electrified lines is presented. The main ideas of determination of economic efficiency for electrification of railways are substantiated.